Partial oxidation of methane using silver/gadolinia-doped ceria composite membranes - Ruiz-Trejo,E; Boldrin,P; Medley-Hallam,JL; Darr,J; Atkinson,A; Brandon,NP (Chemical Engineering Science, 2015)
Methane was partially oxidised to CO using oxygen permeated through a 1 mm thick silver/Ce0.9Gd0.1O2−x (Ag/CGO) composite membrane operating at 500–700 °C with air at 1 bar pressure. The membranes were fabricated by sintering ultrafine nanoparticles of gadolinia-doped ceria (<5 nm) coated with silver using Tollens reaction. This unique combination led to dense composites with low content of silver (7 vol%), no reaction between the components and predominant metallic conductivity. When feeding 4% methane at 700 °C to a 1-mm thick Ag/CGO using Ni as reforming catalyst, the conversion reached 21% and the CO selectivity 92% with an estimated oxygen flux of 0.18 mL min−1 cm−2 (NTP). The samples were stable in carbon-containing atmospheres and under a large pO2 transmembrane pressure difference at temperatures below 700 °C for 48 h.